4(x-6)=-6

Simple and best practice solution for 4(x-6)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-6)=-6 equation:


Simplifying
4(x + -6) = -6

Reorder the terms:
4(-6 + x) = -6
(-6 * 4 + x * 4) = -6
(-24 + 4x) = -6

Solving
-24 + 4x = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 4x = -6 + 24

Combine like terms: -24 + 24 = 0
0 + 4x = -6 + 24
4x = -6 + 24

Combine like terms: -6 + 24 = 18
4x = 18

Divide each side by '4'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| X+20=5-x | | 220=-4+8P | | 2xy-6x= | | 36x^2-96x+36=0 | | 4(n+20)=100 | | 4(n+20)=4n+80 | | 4(n+20)=4n+20 | | 26x^2-36y^2=81 | | 314/75(7.75)^3 | | 6-y=-6 | | 4/3*3.14(7.75)^3 | | 253-5x=40x+17 | | 15-9x=2x-7 | | 3x^2-5x+2y-4=0 | | 3y/6 | | (-5)-(-8)-4y+(-4x)-(-7y)-(-10x)= | | 77+5(x+9)=x | | 9x-(-7y)-(-6)+9-(-2x)-4y= | | (-x)-(-6)+(-4x)+(-7y)-1-8y= | | (-8)+(-8x)+(-y)+4+(-x)+(-9y)= | | -4a^3*2b^2= | | (-8y)-1+y+(-x)-3x-(-8)= | | 10x^24=56 | | 6x-293=6x-13 | | 3y+4+6x-3x-2y-2= | | 10y-6x+4-4x+6y-6= | | 5y-2y+5x+4x-7+9= | | b*c*d*c= | | 3y-1-2y-2x+8-4x= | | a*b*-3*-3= | | 64-6x=8-10x | | p*6*q*-1= |

Equations solver categories